Transtornos traumáticos cumulativos em operadores de caixas bancários - Monticelli, José Antonio (2012)
This research presents an approach of a socio-occupational physical disorders that are subject operators tellers due to their occupational activities are, in general, repetitive - RSI / WMSD and / or its new name Cumulative Trauma Disorders (TTC). Discusses management concepts in banking, as well as the relationship between the different agencies that have the responsibility of ensuring the safety and health of workers banking, ie: FENABAN (employer), Bank Workers (employees) and MPS / INSS (retirement due to the disorder). Complemented by an analysis of statistical data of occurrences of RSI / WMSD TTC-sharing and crossing the information provided by the responsible agencies (cited above) and the benefits already achieved and those yet to be the. Back as a result of the study a true picture of this amazing social occupational category, subject to one of the most recurrent illnesses and what has been done so far was insufficient for the solution and / or minimize these occurrences level in Brazil. And the solution of outsourcing some services that were made in the corresponding bank branches (Lottery, post office, pharmacy, etc.) Only served to outsource the occurrence of this disease in people NOT-bank, but, anyway, PEOPLE.